1992
DOI: 10.1007/bf00232160
|View full text |Cite
|
Sign up to set email alerts
|

Growth and rosmarinic acid production in cell suspension cultures of Salvia officinalis L.

Abstract: Rosmarinic acid (RA) is a natural antioxidant produced by cell suspension cultures of sage (Salvia officinalis L.). The growth and production of RA by these cells can be modified by the type of culture medium. Production can be increased 10-fold to attain 6.4 g.1(-1) under optimal conditions. Investigation of kinetics showed that a change in the medium caused shifts in peaks of growth and production, and modifications of the cell metabolism. RA production can be correlated with growth or begins only when growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
1
4

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(48 citation statements)
references
References 10 publications
4
39
1
4
Order By: Relevance
“…The amounts were twice as high as that in roots of both naturally growing and in vitro regenerated plants (Table 1). It was earlier demonstrated, that RA was produced in in vitro cultures of broad range of plant species including cultures of S. officinalis, in which RA concentration varied from 1.4% up to 36% of dry weight, after optimization of culture conditions (Whitaker et al 1984;Hippolyte et al 1992). On the other hand, Gomes et al (2002) reported a maximum production of 2.8 mg g -1 RA of dry weight from the sage shoot culture i.e.…”
Section: Production Of Antioxidant Compounds In In Vitro Culturesmentioning
confidence: 95%
See 2 more Smart Citations
“…The amounts were twice as high as that in roots of both naturally growing and in vitro regenerated plants (Table 1). It was earlier demonstrated, that RA was produced in in vitro cultures of broad range of plant species including cultures of S. officinalis, in which RA concentration varied from 1.4% up to 36% of dry weight, after optimization of culture conditions (Whitaker et al 1984;Hippolyte et al 1992). On the other hand, Gomes et al (2002) reported a maximum production of 2.8 mg g -1 RA of dry weight from the sage shoot culture i.e.…”
Section: Production Of Antioxidant Compounds In In Vitro Culturesmentioning
confidence: 95%
“…According to observations of many investigators and the results of our work it has been shown that accumulation of RA is not determined by a degree of culture differentiation. The ability to synthesize RA by in vitro cultures is rather dependent on plant species, cell line and its age (Whitaker et al 1984;Hippolyte et al 1992;Del Bano et al 2003). This is the case with sage cell suspension obtained in this work, which after seven passages produced 13.7 mg g -1 of RA on the basis of dry weight.…”
Section: Production Of Antioxidant Compounds In In Vitro Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultivation was performed in Erlenmeyer flasks with 1/5 net volume on the shaker (11,6 rad.sec-1 ) for 12 days. For inoculation 20 % (V IV) of the respective cell suspension was used, cultivated under the described conditions for 7 days.…”
Section: Methodsmentioning
confidence: 99%
“…Extraction of phenolic compounds. The cell and culture medium were separated by filtration, lyophilised and e},.1facted with methanol according Hippolyte et al (6). The methanol extract was concentrated under vacuum to the appropriate volume and was used to follow the time course of phenolics formation and to identify the main phenolics, synthesised and secreted from Lavandula vera-MM.…”
Section: Methodsmentioning
confidence: 99%